Intimate partner violence: gender issues and the adjudication of homicide and other cases. Issue 4 (4th October 2018) - Hamel, John
Abstract : Purpose: The purpose of this paper is to explore the role of gender in intimate partner violence (IPV) and, based upon the author's experience as an expert witness, 25 years of clinical experience working with IPV perpetrators and victims, and a review of the relevant scholarly literature, provide judges, attorneys, mental health professionals and expert court witness suggestions for the adjudication of cases involving IPV in homicide and other cases. Design/methodology/approach: The author reviewed the extant general domestic violence research literature, depending largely on results from findings from the Partner Abuse State of Knowledge Project, a series of 17 literature review published in five issues of the peer-reviewed journal, Partner Ause. Other relevant research articles were found via a search of the PschInfo database, using the keywords "intimate partner homicides, " "domestic violence homicides, " "intimate partner homicides and gender" and "domestic violence homicides and gender." Findings: The judicial response to IPV perpetration has been limited by common misconceptions, among them the confusion between most forms of IPV, which are primarily bi-directional and less consequential and battering, which involves more serious assaults and is typically motivated out of a desire to dominate and control one's partner. Another misconception is that women are much more likely than men to perpetrate IPV in self-defense or to express emotion. On the other hand, there is no question that female victims are much more likely to experience severe physical injuries, and that women account for approximately three-quarters of homicide victims. Practical implications: These include the following: this concise review of IPV research provides a clearer understanding of IPV, useful for anyone working in the field. Mental health professionals working with IPV perpetrators, as well as victims, can draw from this research best practice suggestions in working with more problematic cases. The paper should be especially useful to anyone involved in the adjudication of IPV cases, including lethal cases. In particular, prosecutors and attorneys working for the defense are given suggestions on how to obtain more reliable research data, choose more fruitful questions for their clients, and better conceptualize a case overall. Originality/value: This paper presents a more nuanced and evidence-based conceptualization of serious and lethal IPV, drawing on a broad research base not generally available to members of the legal profession.